2020
DOI: 10.12998/wjcc.v8.i17.3890
|View full text |Cite
|
Sign up to set email alerts
|

Surgical strategy used in multilevel cervical disc replacement and cervical hybrid surgery: Four case reports

Abstract: BACKGROUND Multilevel artificial cervical disc replacement and anterior hybrid surgery have been introduced as reliable treatments for multilevel cervical degenerative disc disease. Surgical techniques are important for resolving patients’ symptoms and maintaining the normal functioning of cervical implants. However, the use of inappropriate surgical strategies could lead to complications such as implant migration and neurological deficit. In this paper, we summarize our surgical strategies used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It is worth noting that the hybrid strategy chosen in this study was ACDF + CDA, and any changes to the hybrid strategy may have a certain impact on the results. 33,34 Previous studies have shown that the biomechanics of hybrid surgery are not only significantly related to the hybrid strategy and the selection of artificial discs, but also influenced by the severity of degenerated segments and the surgical sequence.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the hybrid strategy chosen in this study was ACDF + CDA, and any changes to the hybrid strategy may have a certain impact on the results. 33,34 Previous studies have shown that the biomechanics of hybrid surgery are not only significantly related to the hybrid strategy and the selection of artificial discs, but also influenced by the severity of degenerated segments and the surgical sequence.…”
Section: Discussionmentioning
confidence: 99%
“…41 In addition, intraoperative radiographic confirmation is performed during each step of the implantation process. 42 All these procedures guarantee a proper position of the implanted artificial discs.…”
Section: Discussionmentioning
confidence: 99%
“…In all circumstances the C-ADR should be implanted prior to the ACDF portion of the procedure. If implanting more than one arthroplasty, all trialing, rasping, drilling for both prostheses should be performed prior to C-ADR implantation [41,43].…”
Section: Sequence Of Implantationmentioning
confidence: 99%